Studi Literatur Review: Kemampuan Berpikir Komputasi Matematis Siswa Pada Materi Pola Bilangan - Sazatul Asmal; Yahfizham Yahfizham (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Computational thinking is something that students must have. At this time, quite a few students have difficulty when they are given problems with high level thinking skills. For this reason, this research focuses on analyzing students' mathematical computational thinking on number pattern material. This research takes the type of literature study research by identifying and evaluating the results of previous research. In this research, 3 previous journals were identified. From the results of this research, it was found that students' mathematical computational thinking abilities were still relatively low. For this reason, in the future we should think about this computing being more applied.